How Stigma and Discrimination Influences Nursing Care of Persons Diagnosed with Mental Illness: A Systematic Review. (1st February 2021) - Tyerman, Jane; Patovirta, Autumn-Lee; Celestini, Ann
Abstract: One in four people in the world will be affected by mental illness in their lifetime, placing mental disorders as the leading cause of disability worldwide. This qualitative systematic review was to explore perceived stigma and discrimination experienced by individuals seeking care for physical or mental health concerns. Specifically, it sought to uncover the level of perceived stigma and discrimination experienced by mentally ill patients seeking care for physical or mental health concerns. Seven databases were searched between January 1, 2007 to November 1, 2018. Selected studies met the following inclusion criteria: 1) English language and published within North America, Australia, or United Kingdom; 2) studies and articles that consider individuals with mental illness seeking help for either mental or physical conditions in the hospital setting except for within mental health wards; and 3) research in which the phenomenon of interest examined how stigma and discrimination influences the perception of nursing care received by the mentally ill patient and the perception of nurses who provide care to the mentally ill patient. Eight studies met the inclusion criteria. Studies reported that both patients and nurses perceive similar barriers to person-centered care resulting from stigma toward mental illness. This significantly compromised quality person-centered care, and negatively affected the nurse-client relationship. Results indicate the need for further research to determine how health care and educational institutions play a role in perpetuating stigma against mental illness through the prioritization of physical illness over mental illness.